Writing the experience? Family, identity and intellectual reflection in Inés Joyes (18th century) - Bolufer Peruga, Mónica Bolufer Peruga (Arenal. Revista de historia de las mujeres, 2006)
This essay puts forward an interpretation of Inés Joyes=s Apología de las mujeres (Apology of women, 1798) as a reflection induced by experience, going along with current interest in women's agency and with critiques towards the too rigid notion of Apublic and private spheres. Inés Joyes's life and work, as those of many of her contemporaries, took place in social spaces which have to be interpreted in more complex ways, and contributed to resignify the meanings of family, marriage, maternity, but also social relations and intellectual activity.